Setting up and configuring a new PC - Halsey, Mike (O'Reilly Media, 2012)
"Tis the holiday season bringing gifts of new computers for young and old. In this webcast, Mike Halsey the author of Troubleshooting Windows 7 Inside Out and the forthcoming Windows 8 Step by Step, cuts through the mess of pre-installed bloatware and shows you how to set up your computer system so that it will give you a trouble free, and performance-boosted life. This webcast comes with free downloadable easy guides you can print and keep"--Resource description page.